2003
DOI: 10.1034/j.1600-6143.2003.30108.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Vascular Alterations in Isolated Small‐Bowel Allografts: Relationship to Humoral Sensitization

Abstract: Acute vascular rejection (AVR) in human small-bowel transplantation is an inadequately characterized entity whose frequency and severity is not well understood. As compared to severe AVR, changes identifying early, mild or evolving AVR are not known. We created a scoring system to evaluate subtle mucosal vascular changes and examined 188 biopsies from 21 patients obtained in the first 3 months post transplant. A majority of patients had a transient rise in vascular injury, often within 30 days of transplant. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…During one study using C4d staining, the authors concluded there was a limited relevance of C4d (16). Another study suggested that vascular injury is partially associated with humoral presensitization and could be a form of acute vascular rejection (11). In a third study, the development of DSA was shown to be significantly associated with acute rejection (AR) episodes (10).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…During one study using C4d staining, the authors concluded there was a limited relevance of C4d (16). Another study suggested that vascular injury is partially associated with humoral presensitization and could be a form of acute vascular rejection (11). In a third study, the development of DSA was shown to be significantly associated with acute rejection (AR) episodes (10).…”
Section: Introductionmentioning
confidence: 99%
“…The surrounding interstitium was assessed for the presence of extravasated erythrocytes and edema (11).…”
Section: Gradementioning
confidence: 99%
See 3 more Smart Citations